Comprehensive Characterization of Gelatin Films from Goat Skin Incorporating Konjac Glucomannan: Physical, Mechanical, and Molecular Properties - Hasdar, Muhamad; Nalinanon, Sitthipong; Kittiphattanabawon, Phanat; Sriket, Chodsana (Indonesian Journal of Science and Technology, 2024)
This study aimed to comprehensively investigate and characterize the physical, mechanical, and molecular properties of gelatin films made from goat skin incorporated with konjac glucomannan. The study involved three treatment groups, labeled GG/KG1, GG/KG2, and GG/KG3, which included konjac glucomannan at concentrations of 0, 10, and 20% (w/w), respectively. Glycerol at 20% (w/w) was also included as a plasticizer. All samples underwent homogenization and ultrasonic treatment. The addition of konjac glucomannan to the gelatin-based film resulted in changes such as increased thickness (0.033 - 0.093 mm), opacity (0.9910 - 1.0433 mm-1), color L* (92.45 - 92.77), color difference (48.13 - 48.38), swelling (65.53 - 69.47%), and contact angle (86.92 - 127.85o). Conversely, a decrease was observed in water activity (0.521 - 0.463 Aw), moisture content (9.87 - 9.62%), tensile strength (0.0171 - 0.0118 N/mm2), elongation at break (5.91 - 4.52%), young’s modulus (0.0029 - 0.0026 N/mm²), WVTR (118.99 - 116.82 g/m². day), transparency (81.59 - 67.33%), and water resistance (34.47 - 30.53 %). Additionally, the peaks of amides A, B, I, II, and III exhibit both a shift and an increase in intensity, suggesting structural modifications and molecular interactions. The microstructure also indicated the presence of goat skin gelatin and konjac glucomannan cross-linked in the film formation. Therefore, the addition of konjac glucomannan modifies gelatin-based films, enhancing their suitability for food packaging.